Ecosystem approaches to the better management of brucellosis and toxoplasmosis in Yunnan Province, China - Wengui Li; Unger, Fred; Xiangdong Yang; Shibiao Yang; Gilbert, Jeffrey; Jing Fang; Guorong Yang (Veterinary Public Health Centre for Asia Pacific, 2013)
Brucellosis and Toxoplasmosis are zoonoses of concern in many countries of Asia and Southeast Asia including China despite of ongoing control efforts. To face this challenge, new approaches are required such as Ecohealth targeting on transdiciplinary collaboration. In the presented research, a part of ILRI’s Ecozd project, veterinary, public health, animal science experts from five provincial institutions, practitioners from the project sites, and policy authorities from the provincial Department of Health and Department of Agricultural worked together to understand perception, awareness and behavior of stakeholders, investigate the impact of these diseases and demonstrate how an integrated approach can help to improve collaboration between different stakeholders and contribute to a better control. The research was carried out in Mangshi County and Yiliang City of Yunnan and research activities consisted of historical data review, biological sampling, questionnaires, Focus Group Discussion and In Depth Interview. Also Outcome Mapping was used as an evaluation tool for changing of behavior of targeted groups. Results from biological sampling indicate Brucellosis as a PH hazard anyhow sporadic, while Toxoplasmosis is endemic, both in ruminants and human in the selected regions. Potential risk factors for the spread of these zoonoses exist. Awareness and zoonoses knowledge of potential risk groups was in general low. The use of a “learning by doing” EcoHealth approach in this study has improved team members capacity on Ecohealth and its practical realization in a field study. Outcome mapping indicated a change of behavior in targeted groups, especially on zoonoses knowledge and willingness to share of information.